Slow Wave Sleep and Long Duration Spaceflight - Arias, D.; Whitmire, A.; Leveton, L.; Orr, M. (2011)
To review the literature on slow wave sleep (SWS) in long duration space flight, and place this within the context of the broader literature on SWS particularly with respect to analogous environments such as the Antarctic. Explore how SWS could be measured within the International Space Station (ISS) context with the aim to utilize the ISS as an analog for future extra-orbital long duration missions. Discuss the potential use of emergent minimally intrusive wireless technologies like ZEO for integrated prelaunch, flight, and return to Earth analysis and optimization of SWS (and general quality of sleep).